THE LEVbLS OF MAIN ORGANIC CONSTITUENTS IN THREE EDIBLE FRESHWATER FISHES - Rao, K R S Sambasiva; Padmavathi, P (Indian Journal of Fisheries, 2011)
The levels of total carbohydrates, total proteins, lipids, glycogen, free amino acids and free fatty acids are highest in Channa punctatus followed by Mystus vittatus and Tilapia mossambica. The study also showed liver to be the metabolically active tissue, followed by muscle and gill tissues